2019
DOI: 10.1186/s41936-019-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Camellia sinensis on Syzygium aromaticum- or chlorpyrifos-induced reproductive toxicity in male Wistar rats

Abstract: Background: The potential toxicity of clove, Syzygium aromaticum, notwithstanding its beneficial health effect to human health remains a critical issue. Purpose: This study was designed to assess the effects of oil extracts of clove (S. aromaticum) on reproductive parameters in Wistar rats. The ameliorative effect due to co-administration with green tea, Camellia sinensis, was also determined. Methods: Adult rats were exposed via oral gavage to mineral oil (negative control), 5% green tea (GT), 12.5 mg/kg/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(31 reference statements)
0
1
1
Order By: Relevance
“…The increment in ovarian weight can be attributed to synergetic activity of follicles stimulating hormone and luteinizing hormone triggered by dietary SLM in the bird's diet that enhanced the level of oestrogen secretion which resulted into improvement of the weight of the entire reproductive tract. However, this finding disagreed with the findings of Akinwande et al (2019) and Okukpe et al (2018) who reported a decrease in follicle stimulating hormone secretion in male wistar rats and buck respectively fed clove extract. Infundibulum and magnum length were significantly higher (p<0.05) among hen fed 0.25 and 0.50% SLM.…”
Section: Resultscontrasting
confidence: 99%
“…The increment in ovarian weight can be attributed to synergetic activity of follicles stimulating hormone and luteinizing hormone triggered by dietary SLM in the bird's diet that enhanced the level of oestrogen secretion which resulted into improvement of the weight of the entire reproductive tract. However, this finding disagreed with the findings of Akinwande et al (2019) and Okukpe et al (2018) who reported a decrease in follicle stimulating hormone secretion in male wistar rats and buck respectively fed clove extract. Infundibulum and magnum length were significantly higher (p<0.05) among hen fed 0.25 and 0.50% SLM.…”
Section: Resultscontrasting
confidence: 99%
“… Kata (2018) stated that dichlorvos pesticide-induced a significant increase in sperm abnormalities in male mice treated intraperitoneal for 15 days. Akinwande et al . (2019) have reported that rats treated with chlorpyrifos pesticide for 3 weeks have a higher frequency of sperm abnormalities, especially at the tail and neck regions.…”
Section: Discussionmentioning
confidence: 99%